The Impact of Authoritarian Parenting on Aggressive Behavior in Adolescents - Adelia Marsella; Aliza Cahya Fadhilah; Anisyah Astriasari; Alfina Tri Hapsari; Dewi Franshisca; Salsabila Dwi Putri (CV. Doki Course and Training, 2025)
This study aims to explore the impact of authoritarian parenting on aggressive behavior in adolescents. Aggressive behavior during adolescence is often expressed verbally through insults or threats, and physically through fighting or violence, and it is influenced by the parenting style applied at home. Authoritarian parenting, characterized by strict rules, high demands, one-way communication, and the use of punishment, is suspected to contribute to the emergence of aggression. This research employed a qualitative descriptive method with data collection techniques including participatory observation, in-depth interviews, and documentation. The participants consisted of students in SMK Muhammadiyah 1 Palembang who were identified as experiencing authoritarian parenting patterns. The results revealed that adolescents raised with authoritarian parenting tend to show aggressive behaviors such as shouting, mocking, pushing, or hitting peers, which often emerge as an outlet for frustration due to strict parental control. These findings are in line with Baumrind’s parenting theory and the frustration–aggression hypothesis, which highlight the negative effects of excessive control and lack of emotional support. The study concludes that authoritarian parenting significantly increases the risk of aggressive behavior in adolescents, while democratic parenting approaches are more effective in fostering emotional regulation, mutual respect, and healthy social interaction. This research provides important implications for parents, educators, and counselors in designing preventive strategies and interventions to reduce aggression among adolescents.